2023
DOI: 10.3390/pr11082277
|View full text |Cite
|
Sign up to set email alerts
|

Steam Explosion of Eucalyptus grandis Sawdust for Ethanol Production within a Biorefinery Approach

Abstract: In this work, Eucalyptus grandis sawdust was subjected to steam explosion as the first step in cellulosic ethanol production within a biorefinery approach. The effect of the moisture content in the eucalypt sawdust (8 and 50%) and pretreatment process variables, such as temperature and residence time, were evaluated along with the influence of the water washing of steam-exploded solids on enzymatic hydrolysis and C6 fermentation yields. All other process streams were characterized to evaluate the recovery yiel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…These sugars' yields are quite close to those (69% for glucan and 79% for xylan conversion) previously reported [26] for the enzymatic hydrolysis of eucalyptus bark, subject to the same steam explosion pretreatment, by applying a lower enzyme dosage (3% (w/w)) to a lower solid load (17.5% (w/v)) under a batch configuration. Also, Guigou et al [27] reported efficiencies of 66% for enzymatic hydrolysis of Eucalyptus grandis sawdust, at 15% (w/v) solid load, following pretreatment by steam explosion (205 • C for 10 min). The pre-liquefaction and enzymatic hydrolysis steps were simulated in Aspen Plus with an RStoic reactor based on the reactions and respective conversions.…”
Section: Enzymatic Hydrolysis (Eh)mentioning
confidence: 99%
“…These sugars' yields are quite close to those (69% for glucan and 79% for xylan conversion) previously reported [26] for the enzymatic hydrolysis of eucalyptus bark, subject to the same steam explosion pretreatment, by applying a lower enzyme dosage (3% (w/w)) to a lower solid load (17.5% (w/v)) under a batch configuration. Also, Guigou et al [27] reported efficiencies of 66% for enzymatic hydrolysis of Eucalyptus grandis sawdust, at 15% (w/v) solid load, following pretreatment by steam explosion (205 • C for 10 min). The pre-liquefaction and enzymatic hydrolysis steps were simulated in Aspen Plus with an RStoic reactor based on the reactions and respective conversions.…”
Section: Enzymatic Hydrolysis (Eh)mentioning
confidence: 99%
“…Several works using the fed-batch SSF approach have been performed using different raw materials and pretreatments, demonstrating the feasibility of this strategy, not only due to the improvement of the ethanol concentration obtained, but also due to the product yields achieved [17,23]. Guigou et al [24] published a comparison of ethanol yields and concentrations achieved using different species of Eucalyptus, with initial solid percentages ranging from 4%wt to 27%wt and concentrations between 5.4 g/L to 30.7 g/L. The highest ethanol concentration was achieved using the presaccharification and simultaneous fermentation (PSSF) strategy for Eucalyptus grandis pretreated by steam explosion and S. cerevisiae PE-2 as the fermentative microorganism.…”
Section: Introductionmentioning
confidence: 99%